Light-ion production in 175 MeV neutron-induced reactions on oxygen - Tippawan U. (2017)
Data on light-ion production in light nuclei such as carbon, nitrogen and oxygen are particularly important in calculations of dose distributions in human tissue for radiation therapy at neutron beams, and for dosimetry of high energy neutrons produced by high-energy cosmic radiation inter- acting with nuclei (nitrogen and oxygen) in the atmosphere. When studying neutron dose effects, special consideration on carbon and oxygen is needed since they are, by weight, the most abun- dant elements in human tissue. The MEDLEY setup at The Svedberg Laboratory (TSL), Uppsala, Sweden has been used to measure such data with double-differential cross sections (DDX) for the (n, xp), (n, xd), (n, xt), (n, 3 He), and (n,α) reactions from C, O, Si, Ca, Fe, Pb, and U around 96 MeV. At the new Uppsala neutron beam facility the available energy range of quasi mono-energetic neutron beams is extended up to 175 MeV. The detector setup used in MEDLEY consists of eight so-called telescopes mounted at different angles inside an evacuated reaction chamber. Each of the telescopes consists of two fully depleted ΔE silicon surface barrier detectors (SSBD) and a CsI(Tl) crystal. In order to make measurements at this higher neutron energy possible some changes in the detector setup compared to the campaign at 96 MeV were applied Accordingly, the second ΔE detectors have been replaced by 1000 μm thick SSBDs as well as the size of the crystals used as E detectors was increased to a total length of 100 mm and a diameter of 50 mm. The ΔE-E technique is used to identify the light ions, and cutoff energies as low as 2.5 MeV for protons and 4.0 MeV for alpha particles are achieved. The data are normalised relative to elastic np scattering measured in one of the telescopes at 20 degrees. Preliminary DDXs for oxygen are presented and compared with theoretical calculations.